The house on Burra Burra Lane - Jones, Jennie (Chatswood : Escape Publishing, 2013)
A dilapidated house, a city girl looking for a tree change, and a rugged vet with a past. Just another day in rural Australia... Just ten days after her fresh start in the isolated Snowy Mountains, Samantha Walker trips over a three hundred pound pig and lands in the arms of Dr. Ethan Granger - and the firing line for gossip. It was hardly a 'date' but sparks of the sensual kind are difficult to smother in a community of only 87 people. Now there's a bet running on how long she'll stay and what she'll get up to while she's in town. Ethan has his own issues - Sammy's presence in his childhood home brings with it painful recollections of family scandals and a bad boy youth. When the gossip around them heightens, his life is suddenly a deck of cards spread on the table for all to see. Then Sammy's past catches up with her... and it looks like all bets are off.
Imprint: Escape Publishing.
Description based on online resource; title from EPUB title page (OverDrive, viewed May 29, 2013)
Keywords: Country homes -- Fiction; Single women -- Fiction; Veterinarians -- Fiction; Veterinarians -- Australia -- Snowy Mountains (N.S.W.) -- Fiction; Veterinarians -- New South Wales -- Snowy Mountains -- Fiction; Country homes; Fiction - Romance - Contemporary; Fiction - Romance - Contemporary; Fiction - Romance - Western; Fiction - Romance - Western; FICTION / Romance / Contemporary; Single women; Veterinarians; New South Wales -- Snowy Mountains; Australian; Love stories; Electronic books; Fiction